The Analysis of Collocations Use the Film Entitled “Rambo: Last Blood” By Adrian Grunberg - Rosanna Marpaung; Musawer Hakimi; Jontra Jusat Pangaribuan (Journal of Language Education (JoLE), 2024)
Collocation is defined as a combination of words in a language, which occurs very often and more often than happens by chance. The aims of this study were to find out What are the types of collocations that used in the film entitled "Rambo: Last Blood" by Adrian Grunberg? And to To find out the dominant type of collocation in the collocation of the film entitled: "Rambo: Last Blood " by Adrian Grunberg. This study used a qualitative descriptive method would use to analyze data which is a collocation contained in the film's subtitle. The data source in this study is the subtitled transcript of the film “Rambo: Last Blood “by Adrian Grunberg, which was taken from the translation of the Netflix application. The data in this study are English collocations contained in the film subtitle “Rambo: Last Blood” and its translation into Indonesian in the form of phrases. From the result we can be seen that the maximum percentage is 70% and the minimum percentage is 30% and it can be concluded that the dominant type of collocation results in the collocation of the film entitled: "Rambo: Last Blood" by Adrian Grunberg is Lexical Collocation with a presentation result was 70%. So the dominant collocation that used in of the film entitled: "Rambo: Last Blood" by Adrian Grunberg is Lexical Collocation (70%) because showed the significant precentence.